Tierras ejidales ¿Mercancía o territorios indígenas? - Gabriela Torres-Mazuera (Caravelle)
Conflicts associated with granted and restored lands, as ejidos and communidades, during Mexican agrarian reform (1915-1992) are increasing. There are various causes, all specifically related to the processes of privatization and commodification of these lands, invigorated in 1992 with a legal reform that allows their alienation. The argument of this work is that the role of the intermediation in case of agrarian conflict by agrarian officials, magistrates and lawyers is more important than ever. This, in a context of neoliberal and multicultural legal reforms that distort but don’t eliminate the principles of social rights associated with ejido and communal lands, when it comes to their defense as territory or their transfer as merchandise.